1996
DOI: 10.4319/lo.1996.41.4.0605
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for aging food patches as a factor contributing to high deep‐sea macrofaunal diversity

Abstract: To determine whether deep‐sea macrofaunal succession is observed in response to small‐scale patches, we deployed colonization trays at 900‐m depth for 23 d and 28 months. Treatments included sediment that was unenriched or enriched with Sargassum natans. Short‐term Sargassum trays contained significantly higher and short‐term unenriched trays significantly lower total densities than the ambient sediment. Both Sargassum treatments attracted high densities of a low‐diversity fauna, but they differed in species c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 26 publications
4
26
0
1
Order By: Relevance
“…Other relatively short-term colonization experiments using a similar tray apparatus have yielded a variety of results. In a 23 day experiment in the Northwest Atlantic, macrofaunal densities in Thalassiosira and Sargassum-enriched trays reached 66 450 ind m −2 and 16 000 ind m −2 , respectively, greatly exceeding ambient densities (Snelgrove et al, 1994(Snelgrove et al, , 1996. However, the unenriched controls did not exhibit the same ambient density overshoot seen in the enriched trays (Snelgrove, 1994(Snelgrove, , 1996.…”
Section: Density: Ambient Vs Colonizing Faunamentioning
confidence: 93%
See 3 more Smart Citations
“…Other relatively short-term colonization experiments using a similar tray apparatus have yielded a variety of results. In a 23 day experiment in the Northwest Atlantic, macrofaunal densities in Thalassiosira and Sargassum-enriched trays reached 66 450 ind m −2 and 16 000 ind m −2 , respectively, greatly exceeding ambient densities (Snelgrove et al, 1994(Snelgrove et al, , 1996. However, the unenriched controls did not exhibit the same ambient density overshoot seen in the enriched trays (Snelgrove, 1994(Snelgrove, , 1996.…”
Section: Density: Ambient Vs Colonizing Faunamentioning
confidence: 93%
“…The colonization trays consisted of an 11.1 cm diameter central cup (9 cm deep) lined with 20 µm mesh, surrounded by a flat delrin nylon collar 40 cm in diameter. The design of the colonization trays is described by Levin and DiBacco (1995) and is identical to those used by Snelgrove et al (1992Snelgrove et al ( , 1994Snelgrove et al ( , 1996 in the Atlantic Ocean and Levin et al (2006Levin et al ( , 2013 in the Pacific Ocean. The broad collar is designed to reduce turbulent flow over the central cup and prevent scour.…”
Section: Colonization Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sediment percentage total organic carbon (%TOC) concentrations are the most widely available sedimentary parameter for representing the flux of particulate OM (POM) to the sea floor (Seiter et al 2004;2005), which exhibits significant regional variability (Lutz et al 2002). These concentrations can be a useful measure of resources available to support benthic biota (Snelgrove et al 1992) because positive relationships have been observed between %TOC and benthic biodiversity (Snelgrove and Butman 1994;Snelgrove et al 1996). %TOC is often inversely correlated with grain size (Mayer 1994;Keil et al 1997) because ,99% of sedimentary OM occurs in fine fractions as discontinuous blebs on clay surfaces (Ransom et al 1997).…”
Section: Introductionmentioning
confidence: 99%